PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS V SDN 5 SINGKAWANG - Sepsepania Rosmalita; Slamat Fitriyadi, Dewi Mariana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to: 1) The application of the role playing learning model to the speaking skills of grade V students of SDN 5 Singkawang, 2) Improve speaking skills with the role playing model in grade V students of SDN 5 Singkawang, 3) Determine the effectiveness of the application of the role playing learning model to improve speaking skills in grade V students of SDN 5 Singkawang. The type of research used in this study is quantitative. The population in this study is grade V students of SDN 5 Singkawang with a One-Group Pretest-Posttest Design research design.The data collection technique in data collection research is the measurement technique. The data analysis techniques are the Kolmogorov-Smirnov Test, the Levene's Test, the Independent Sample T-Test and the N-Gain Test. The results of the study show that 1) The application of the Role Playing method after obtaining Pretest and Postest data, the results of the sig (2-tailed) value were 0.000 < 0.05 in the sense that there is a significant difference between the Pretest and Post-test scores, and 2) The Role Playing learning model can improve students' speaking skills, especially drama material by 0.33 which is in the medium category.